Financial Development and Economic Growth Nexus: Evidence From Algeria Lien entre développement financier et croissance économique: témoignages de l’Algérie - Hafsaoui, Nour El Houda; Khallout, Allaoua; BOUCHELAGHEM, Amirouche (Finance and Business Economies Review, 2019)
This research paper represents a brief summary of both the theoretical and the empirical frameworks of the most important researches related to the study of the relationship between financial development and economic growth. A standard study was conducted to investigated the nature of the relationship and to determine the role of the Algerian banking system in promoting the economic activity during the period (1990 – 2014) relying on a set of tests, including the test of cointegration of variables, and vector error-correction model. In addition to Granger’s causality, using only the financial variables, and then applying the model using macro variables (financial and real variables) as to identify the most influential factors on economic growth . The study concluded that there is a one-way long-term causal relationship between banking system and economic growth. While the Granger’s causality test indicates a oneway causal relationship between economic growth and investments.